2007
DOI: 10.1111/j.1469-8137.2007.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of cranberry (Vaccinium macrocarpon) with the ericoid mycorrhizal fungus Rhizoscyphus ericae increases nitrate influx

Abstract: Summary• Despite the ubiquitous presence of ericoid mycorrhizal (ERM) fungi in cranberry ( Vaccinium macrocarpon ), no prior studies have examined the effect of ERM colonization on influx kinetics. • Here, influx was measured in nonmycorrhizal and mycorrhizal cranberry in hydroponics. Mycorrhizal cranberry were inoculated with the ERM fungus Rhizoscyphus (syn. Hymenoscyphus ) ericae .influx by R. ericae in solution culture was also measured.• Rhizoscyphus ericae influx kinetics were linear when mycelium was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 86 publications
2
21
1
Order By: Relevance
“…Our results thus disagree with the notion that NO 3 - availability is always negligible in acid soils (Paul and Clark, 1989) but support the claims of Scagel (2005) and Kosola et al (2007) that NO 3 - is an important N source for plants in the family Ericaceae. ERM colonization under acidic soil conditions probably plays a critical role for plants in the heather family to capture NO 3 - -N.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results thus disagree with the notion that NO 3 - availability is always negligible in acid soils (Paul and Clark, 1989) but support the claims of Scagel (2005) and Kosola et al (2007) that NO 3 - is an important N source for plants in the family Ericaceae. ERM colonization under acidic soil conditions probably plays a critical role for plants in the heather family to capture NO 3 - -N.…”
Section: Discussioncontrasting
confidence: 99%
“…An explanation is that cranberry has adapted to acidic soil conditions where pH ranges from 4 to 5 and nitrification is typically negligible at soil pH below 5.5 (Paul and Clark, 1989), therefore the adaptation has resulted in the loss of plant capacity to absorb NO 3 - . However, recent reports showed that inoculation with the fungus Rhizoscyphus ericae increased the capacity of cranberry to absorb NO 3 - (Kosola et al, 2007). Compared to uninoculated plants, inoculating certain blueberry ( Vaccinium corymbosum L.) cultivars with ERM fungi can increase nutrient concentration, particularly N, and plant growth (Scagel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the second greenhouse experiment, plants were transplanted to 4-L pots filled with the same peat and pine bark mix as in Experiment 1 and fertigated with ammonium sulfate or urea mixed in modified Johnson's nutrient solution (Kosola et al, 2007). The fertilizers were applied three times per week, weekly, or every 28 days.…”
Section: Methodsmentioning
confidence: 99%
“…The adaptation to such soil conditions has resulted in the loss of the capacity to absorb NO 3 - . A recent report, however, showed that inoculation with the fungus Rhizoscyphus ericae increased the capacity of cranberry to absorb NO 3 - (Kosola et al, 2007), and the authors believe that NO 3 - may play a greater role in N nutrition of cranberry than previously thought and that high capacity for NO 3 - utilization is the ancestral state for the Ericaceae. Yin et al (2010) also found that ERM fungi significantly increased the ability of R. fortunei to absorb N, especially in the form of nitrate.…”
Section: Introductionmentioning
confidence: 99%